Between terror and solidarity: the influence of the Haitian revolution in the Independence of Venezuela and the New Granade (1804-1825) - Martinez Peria, Juan Francisco (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2016)
In this work I analyze the influence of the Haitian Revolution in the independence of Venezuela and Colombia during the years 1804-1825. My intention is to show that the impacts were vast, complex and underwent significant changes during the course of the years. Overall, the revolution created panic among the local and Spanish elites and hopes among groups of slaves and “pardos” . Initially the revolutionary creoles sought to avoid all contact with the island and avoid the Haitian insurgent model considering that it would produce a race war in Spanish America. However, from 1812-1813 due to the difficulties of the war of independence a faction of the creoles elite began to establish   ties with the Republic of South Haiti through diplomatic contacts and privateers. These early relationships, rather timid, were the condition of possibility of a major change that occurred in 1816. In that year, due to the re-conquest of the royalist expedition, most separatist leaders fled the mainland and were forced to exile in Haiti, one of the few places where they found refuge. In that context, President Alexandre Petion established a pact with Simón Bolivar offering military support in exchange of the abolition of slavery in Spanish America. This agreement turned out to be crucial because it made possible the victorious patriot counteroffensive and because it gave a reformist social dimension to the revolutionary process in Venezuela and Colombia. Thus, from 1816 to 1821, numerous contacts were established and even the government of Jean-Pierre Boyer (successor Alexandre Petion) collaborated with two other expeditions lead by Gregor MacGregor to free Panama and Rio Hacha. However, the change was not complete and even during these years, the creole leaders continued to have anxieties towards the menace of Haitian like revolution exploding in the Spanish mainland. Finally, the end of the war of independence opened a new context in which those fears were intensified due to internal popular mobilization. This led to a new scenario in which the government of Colombia not only refused to maintain relations with Haiti but even excluded this country from the Congress of Panama.